If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18=2(v+1)
We move all terms to the left:
-18-(2(v+1))=0
We calculate terms in parentheses: -(2(v+1)), so:We get rid of parentheses
2(v+1)
We multiply parentheses
2v+2
Back to the equation:
-(2v+2)
-2v-2-18=0
We add all the numbers together, and all the variables
-2v-20=0
We move all terms containing v to the left, all other terms to the right
-2v=20
v=20/-2
v=-10
| 6x-15=2x+12+3x | | 0.5m+1.5=0.25m-1.5 | | 2(f-8)=18 | | 5z+12=2z+6+4z-3 | | 9(d-3)=12d | | 9m-9=10m | | 10=r/2+12 | | 3=2r-15 | | 5•(x+9)=20 | | -4k+10=-5k | | 2x+3(38-x)=116 | | 7v+16=37 | | 4(2x+2)+2x=5(2x-1) | | 9b=10b+3 | | 6w-3=3w+9 | | 5(x+2)-2(3-2x)=3(x-5)-4(4-x) | | 8x+13=29+4x | | 4k-6=14 | | 4+5=-2x+4+7x | | 7+11=-18x+18 | | 2x^2+-11x+-21=0 | | 3x-12+6=5x+5+1 | | 5(x+1)-4(x-2)=2(7+x) | | -2(x+2)=-50 | | 15-2s=9 | | 12x+18=-43+49 | | (7.5*32)+(7.5*1.5)x=273.75 | | 20+X/60=x | | (79/10)-(8/10)x=(23/10) | | 2x+5=6(x-2) | | 4−x/7=10 | | -3b+24-5=19-3b |